2023
DOI: 10.26434/chemrxiv-2023-qpzx3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ChatGPT Needs a Chemistry Tutor Too

Abstract: AI and ChatGPT technology have the potential to revolutionize the education sector, and this study aimed to evaluate if prompt formats, response consistency, and reliability of ChatGPT responses could help colleges make the most of this technology. The results of this study can guide future AI and ChatGPT implementations and ensure they are used to their fullest potential. The data does not demonstrate a statistically significant difference between multiple-choice and free response prompt formats. Neither form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…This investigation adds to previous work investigating the ability of ChatGPT to answer questions found in general chemistry courses , by examining ChatGPT’s output on questions involving acid and base calculations paired with an in-depth analysis of student work on the same questions. A goal of this preliminary study is to assess the chatbot’s output, evaluate its correctness, and compare the chatbot and student responses.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…This investigation adds to previous work investigating the ability of ChatGPT to answer questions found in general chemistry courses , by examining ChatGPT’s output on questions involving acid and base calculations paired with an in-depth analysis of student work on the same questions. A goal of this preliminary study is to assess the chatbot’s output, evaluate its correctness, and compare the chatbot and student responses.…”
Section: Introductionmentioning
confidence: 95%
“…Chatbots, like ChatGPT, are an artificial intelligence resource that have diverse potential uses by instructors and students, such as being used to create assignments or to provide the learner with feedback and explanations. , ChatGPT’s functionality as an automated feedback system parallels that of other systems but with superior natural language processing (NLP) ability. Nascent research into its use in the chemistry , and physics education research communities have examined its ability to answer questions, produce explanations, and contribute to written work like lab reports.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the usefulness of prompting frameworks and the students' use of text-generative AI are described in this context. The work does not aim to verify whether the answers given by AI were correct, as this has been considered many times, 31,32,47 and it is expected that students will tend to rate the answers to be more correct than experts would. 35 Altogether, the main aim of this study is to develop a deeper understanding of prompting skills and to investigate how to implement the Five S framework to develop those skills.…”
Section: Aim Of This Studymentioning
confidence: 99%
“…Furthermore, chemistry questions in multiple-choice and open format of a general chemistry exam were answered with low accuracy. 31,32 As for students, it was shown that AI tools are used by two-thirds of German university students, 33 but they have mediocre AI literacy. 34 There even are reports of unreflected acceptance of ChatGPT's answers when solving physics tasks.…”
Section: ■ Introductionmentioning
confidence: 99%
“…An early investigation using ChatGPT-3.5 to answer chemistry questions found that the chatbot had strong natural language processing skills (NLP) to communicate information, but that the accuracy of the chatbot’s output was a concern . Shortcomings involving the accuracy of ChatGPT-3.5 have since been discussed in early stage reviews of the use of Artificial Intelligence (AI) in educational settings, leading some to conclude that inaccuracies are a serious impediment to its use. , Others have looked closely at the nature of these errors and considered them in relation to student reasoning and problem-solving. Fergus and co-workers found that ChatGPT’s answering of questions involving the interpretation of nontext information and the application of knowledge were weaknesses for the chatbot .…”
Section: Introductionmentioning
confidence: 99%